A 32-year-old obese Male with Prolonged Increased Transaminase Level Associated with NASH after HBV Hepatitis (Journal of Medicine, 2010)
Nonalcoholic steatohepatitis (NASH) is an underdiagnosed liver disease and is the main cause of persistent elevated serum liver enzymes among the general population. Here, we report the case of a 32-year-old obese man who was diagnosed as a case of chronic hepatitis caused by HBV infection. He was treated with Lamivudine for two years. Though his HBV DNA load became negative, he had persistently elevated ALT and AST for two years. Then a liver biopsy was planned for greater diagnostic and prognostic certainty, as the patient was obese, and aspartate transaminase to alanine transaminase ratio was greater than one. The histopathology showed steatosis, ballooning degeneration, microinflammation and fibrosis compatible with non-alcoholic steatohepatitis. We present the case as we think that clinicians should be aware of the possibility, that hepatitis B viral hepatitis with prolonged elevated serum liver enzymes might be associated with non-alcoholic steatohepatitis. Keywords: Non-alcoholic fatty liver, steatohepatitis DOI:10.3329/jom.v11i1.4283 J Medicine 2010: 11: 90-93